Survival Outcomes of Patients With Epidermal Growth Factor Receptor Mutations in Non-Small Cell Lung Cancer With Leptomeningeal Metastasis - Li, Ning; Bian, Zhimin; Cong, Minghua; Liu, Yutao (Frontiers in Oncology, 2022)
Background: Leptomeningeal metastasis (LM) is one of the devastating complications in EGFR-mutated (EGFRm) non-small cell lung cancer (NSCLC). This study aimed to evaluate gene mutations, treatment strategies, and clinical outcomes of combination therapy in the treatment of LM. Methods: We retrospectively reviewed prognostic significance of fifty-three EGFRm NSCLC patients diagnosed with LM. Results: There were fifty-three EGFRm NSCLC with LM(n=53). The median overall survival (OSLM) after LM of the EGFRm NSCLC patients was 13.0 months with a range from 0.5 to 42.0 months (95%CI: 9.067-16.933), and with 64.2% maturity. there was a significant difference in the rate of LM disease control between patients administered Osimertinib or not after LM (35/4 vs. 6/6, respectively; P=0.008). Logistic regression analysis showed that LM-efficacy (P=0.000, exp (b)=10.797, 95% CI=4.102-28.419) was a significant predictive factor for survival after LM. Conclusions: EGFRm NSCLC patients with LM had survival benefits with switched high-level EGFR-TKIs treatment no matter gene mutation status in in tissue and CSF. Patients with LM with peripheral lesions PR or SD and EGFR gene mutation was eliminated in blood, are likely to benefit from the treatment.